2016
DOI: 10.29173/cjs23863
|View full text |Cite
|
Sign up to set email alerts
|

Youth Unemployment and Career Scarring: Social-Psychological Mediating Effects?

Abstract: Unemployment has career scarring effects for adults, and sometimes for youth, but previous research has not directly demonstrated how this occurs. This 14-year (1985-99) longitudinal study reveals that cumulative unemployment between age 18 and age 32 has a negative effect on both total income and quality of employment at age 32. This scarring effect is not mediated by parallel changes in self-esteem, perceived control or extrinsic work values. Labour market mechanisms, rather than social psychological proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Previous research has shown, that youth from less privileged families tend to leave education earlier and are more likely to encounter problems in the transition from school to work, such as experiencing prolonged periods of time spent not being in education, employment or training (NEET) than their more privileged peers (Bynner and Parsons 2002 ; Schoon and Lyons-Amos 2017 , 2016 ). Longer periods of unemployment or economic inactivity during the school-to-work transition are problematic because this can increase the risk of poor occupational and psychological outcomes in the immediate and longer term including lower earnings, persistent unemployment, lower life satisfaction and higher levels of malaise (Bynner and Parsons 2002 ; Krahn and Chow 2016 ; Mroz and Savage 2006 ).…”
Section: A Socio-ecological Model Of Agencymentioning
confidence: 99%
“…Previous research has shown, that youth from less privileged families tend to leave education earlier and are more likely to encounter problems in the transition from school to work, such as experiencing prolonged periods of time spent not being in education, employment or training (NEET) than their more privileged peers (Bynner and Parsons 2002 ; Schoon and Lyons-Amos 2017 , 2016 ). Longer periods of unemployment or economic inactivity during the school-to-work transition are problematic because this can increase the risk of poor occupational and psychological outcomes in the immediate and longer term including lower earnings, persistent unemployment, lower life satisfaction and higher levels of malaise (Bynner and Parsons 2002 ; Krahn and Chow 2016 ; Mroz and Savage 2006 ).…”
Section: A Socio-ecological Model Of Agencymentioning
confidence: 99%
“…On the individual level, several studies have suggested that unemployed young individuals are more likely to have poor physical health [67], increased risk of cardiovascular disease [8], engage more frequently in criminal behaviour [9] and express poorer lifestyle behaviours such as smoking [10], increased alcohol consumption and substance abuse [9, 11]. Furthermore, unemployment in this age group has been associated with higher mortality rates due to suicide [9, 12], alcohol-related mortality [13], lower income and poorer quality of employment later in life [14] and is related to a wide spectrum of mental health problems such as increased stress [4] and psychosomatic symptoms [15], decreased mental wellbeing [16], lower life satisfaction [17], increased risk of depression [18], anxiety [19], other psychiatric disorders [20] and decreased mental health later in life [21].…”
Section: Introductionmentioning
confidence: 99%
“…Being NEET is associated with negative long-term outcomes. Young people who are NEETs now may potentially be trapped in a cycle of unemployment, if not suffer 'wage scarring', a situation wherein their future wages will be much lower than their counterparts who have not been NEET in their youth (Gregg and Tominey [2005]; Krahn and Chow [2016]). They also tend to engage in riskier activities (e.g.…”
Section: Youth Not In Employment Education or Trainingmentioning
confidence: 99%
“…There are costs to being NEET, as evidence shows. Youths in NEETs are penalized in the future for lacking education and employment experience (Gregg and Tominey [2005]; Krahn and Chow [2016]). They are also likely to engage in substance abuse and have poorer health conditions (Bania et al [2019]; Furlong [2006]; Gutiérrez-García et al [2018]; Ling and O'Brien [2013]; Maguire [2015]).…”
Section: Background and Introductionmentioning
confidence: 99%